Modern features of innovative strategies for the development of hotel business enterprises - E. L. Zadneprovskaya; T. N. Poddubnaya; E. A. Panina; T. A. Dzhum (Новые технологии, 2022)
The hotel business is the basic sector of the tourism industry, contributes to the increase in tourist flows, the internationalization of financial capital, and the growth of employment. The hotel sector is developing rapidly (with the exception of 2020, which is explained by anti-Covid measures), largely due to the introduction of innovative development strategies. The investment prospects of the hotel sector should be built on the basis of such a systematization of modern innovative trends, and business planning of the activities of hotel enterprises should ensure the best implementation of innovative approaches when developing a strategy in a specific business environment. The purpose of the study is to study the modern features of innovative strategies for the development of hotel business enterprises, their impact on the dynamics of sales of paid services to the population, including the example of the Krasnodar Territory. The research methods are the following: statistical method, competitive analysis method, generalization method, forecasting. The results and conclusions: an analysis of the applied innovative strategies by hospitality enterprises indicates that such strategies are effective tools for effectively solving the problem of survival and ensuring the business security of hotels. Conclusions: innovative strategies are the most important part of the strategic management of a hotel enterprise, they make it possible to strengthen its competitiveness, meet the constantly changing preferences of guests, follow industry trends or even outstrip them.